Ｂ型肝炎ウイルス感染症を処置するための組合せ療法 (2025)
本開示は、Ｂ型肝炎感染症を処置するための方法に関する。本方法は、それを必要とする対象に、ＰＡＰＤ５／７阻害剤およびＨＢＶ ｍＲＮＡを標的とする修飾ＡＳＯを投与する工程を含む。 The present disclosure is related to methods for treating hepatitis B infections. The methods comprising administering a subject in need thereof a PAPD5/7 inhibitor and a modified ASO that targets HBV mRNAs.